RNA Sequencing Analysis of Metopolophium dirhodum (Walker) (Hemiptera: Aphididae) Reveals the Mechanism Underlying Insecticide Resistance - Gao, Haifeng; Zhu, Xun; Li, Guangkuo; Liu, Enliang; Shen, Yuyang; Zhao, Sifeng; Ge, Feng (Frontiers in Sustainable Food Systems, 2021)
Xinjiang (XJ) and Ningxia (NX) provinces are important agricultural regions in western China. Aphids are one of the most devastating pests in both the provinces. Aphids are typical phloem-feeding insects distributed worldwide and can severely damage crops. In this study, two representative Metopolophium dirhodum (Walker) (Hemiptera: Aphididae) populations were collected from the main agricultural regions of XJ and NX for a high-throughput transcriptome sequencing analysis. A total of 5,265 differentially expressed genes (DEGs) were identified between the populations. The functional annotation of DEGs and the identification of enriched pathways indicated many of the DEGs are involved in processes related to energy metabolism, development, and insecticide resistance. Additionally, an investigation of insecticide toxicity revealed the NX population is more resistant to insecticide treatments than the XJ population. Thus, the transcriptome data generated in this study can be useful for the functional characterization of the genes relevant to aphid development, metabolism, environmental adaptation, and insecticide resistance.